Lutein and zeaxanthin isomers modulates lipid metabolism and the inflammatory state of retina in obesity-induced high-fat diet rodent model - Tuzcu, Mehmet; Orhan, Cemal; Muz, Omer Ersin; Şahin, Nurhan; Juturu, Vijaya; Şahin, Kazım (Bmc, 2017)
Background: Several studies associated high-fat intakes with a high incidence of age-related macular degeneration (AMD). Lutein and Zeaxanthin isomers (L/Zi) may counteract reactive oxygen species produced by oxidative stress. The present study was conducted to determine the possible effects of L/Zi administration on lipid profile, protein genes associated with oxidative stress and inflammation pathways in the obesity induced by a high-fat diet (HFD) in rodents. Methods: Twenty-eight male Wistar rats were allocated into four groups as follows: (i) Control, (ii) Control + L/Zi, (iii) High Fat Diet (HFD), and (iv) HFD+ L/Z. L/Zi was administrated for 8 weeks at a daily dose of 100 mg/kg BW. Results: L/Zi administration significantly reduced insulin and free fatty acid (FFA) levels (P < 0.001) and ameliorated the oxidative damage by reducing malondialdehyde (MDA) concentration and increasing antioxidant enzymes activities of retina induced by HFD. In addition, supplementation decreased the levels of vascular endothelial growth factor (VEGF), inducible nitric oxide synthase (iNOS), nuclear factor-kappa B (NF-kappa B) and intercellular adhesion molecule-1 (ICAM) (P < 0.001, respectively) and improved nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) gene proteins in retinal tissues (P < 0.001). Conclusion: Rats fed with HFD exhibited increased oxidative stress and upregulation of inflammatory indicators. However, L/Zi supplementation modulates genes involved oxidative stress and inflammation including NF-kappa B and Nrf2 signaling pathways in the retina which may contribute to ameliorating retinal damage induced by HFD.
Keywords: High fat diet; Lutein; Zeaxanthin; NF-kappa B; Nrf2; Retina